2012
DOI: 10.1074/jbc.m111.324483
|View full text |Cite
|
Sign up to set email alerts
|

Trimeric, Coiled-coil Extension on Peptide Fusion Inhibitor of HIV-1 Influences Selection of Resistance Pathways

Abstract: Background: N-terminal, heptad repeat (HR1) peptides of HIV envelope glycoprotein form coiled-coil oligomers that inhibit viral entry, but the targets are unclear. Results: An HR1 peptide stabilized as a trimer preferentially selects one resistance pathway, whereas the same unrestrained peptide selects two pathways. Conclusion: Stabilizing the trimer affects development of resistance. Significance: These findings inform inhibitor design and provide insights into virus entry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
56
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(61 citation statements)
references
References 43 publications
4
56
1
Order By: Relevance
“…We estimated the relative stability of different 6HBs by determining their transition mid-point temperature (T m ) in thermal denaturation studies using mixtures of N and C peptides to model 6HB interactions. Using our previous T m values [46,48], as well as additional data obtained in the current study (Table 3), we found a strong correlation between increased resistance and increased 6HB stability (Figure 2A). For example, when the T m increased 20°C, resistance increased five-fold.…”
Section: Effect Of Different Combinations Of Resistance Mutations Onsupporting
confidence: 77%
See 3 more Smart Citations
“…We estimated the relative stability of different 6HBs by determining their transition mid-point temperature (T m ) in thermal denaturation studies using mixtures of N and C peptides to model 6HB interactions. Using our previous T m values [46,48], as well as additional data obtained in the current study (Table 3), we found a strong correlation between increased resistance and increased 6HB stability (Figure 2A). For example, when the T m increased 20°C, resistance increased five-fold.…”
Section: Effect Of Different Combinations Of Resistance Mutations Onsupporting
confidence: 77%
“…Their inhibitory mechanism remains unclear, but current models suggest that N peptides can interfere with HR1 coiled-coil formation, and, especially if stabilized as a trimer, can sequester the HR2 region of the pre-hairpin intermediate [44][45][46]. In either case, as with C peptides, formation of the 6HB is interrupted.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the effect of a single substitution was not evaluated, the authors showed that HIV-1 HXB2 pseudovirions carrying E49K/V59I double substitutions conferred ϳ400-fold resistance to PIE7-dimer. Interestingly, the E49K substitution was also selected by NHR-derived peptides (N44, N36, and IZN36) that might target both NHR and CHR sites (48,49), but the studies showed that the single E49K substitution mediated only mild resistance. In our case, this substitution repeatedly resulted in an ϳ1.5-fold change in resistance to peptide N36 (data not shown).…”
Section: Figmentioning
confidence: 99%